Penerapan Layanan Bimbingan Belajar untuk Meningkatkan Kemampuan Membaca Siswa Kelas IX Sekolah Menengah Pertama - Elsyana Lisa Tambaru; Satri Napa; Ribka Mangalik (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2026)
Reading ability is a fundamental skill that strongly influences the academic success of junior high school students, particularly ninth graders in preparing for national examinations. Nevertheless, many students continue to face difficulties in reading, including speed, comprehension, and motivation. This study aims to examine the effectiveness of implementing learning guidance services to improve the reading skills of ninth-grade students, while identifying supporting and inhibiting factors in its implementation. The research employed a descriptive qualitative approach through literature review from relevant scientific sources published within the last ten years. The findings reveal that learning guidance services play a crucial role in enhancing reading skills, learning motivation, and student independence. Guidance and counseling teachers act as strategic facilitators, while support from the school environment and family strengthens the success of the program. The practical implications highlight that structured, continuous, and collaborative learning guidance programs can help students better understand reading materials and develop positive study habits. Practical recommendations are addressed to teachers, counselors, and schools to design more varied and student-centered guidance services.